Crecimiento y ciclo reproductivo de Polymesoda radiata (Bivalvia: Corbiculidae) en Costa Rica - Ruiz Campos, Eleazar (Universidad de Costa Rica, 1998)
A populationof green clam, Polymesoda radiata was sampledfromAugust 1992 through J uly 1993 in Bebedero river, Guanacaste, Costa Rica (n= 978) fOI demographic data. Mean Yalúes(followed by ranges) were: shell length 32.29 ± 7.63 min (6.9-44.10 mm).